Teachers' conceptions and misconceptions concerning three natural phenomena - Kikas, Eve (Journal of research in science teaching, 2004)
This study focuses on the conceptions of trainee, primary, and subject teachers about three phenomena: the motion of objects, seasonal changes, and aggregate changes of matter. A total of 198 participants completed a questionnaire concerning two types of tasks. First, teachers evaluated the adequacy of a given explanation as compared to their knowledge of the contemporary scientific explanation. Four types of explanations were provided: a simple description, description with terms, an explanation with misconception, and a scientific explanation. Second, respondents answered multiple‐choice questions and substantiated their choices. The findings showed not only various misconceptions but also differences between the phenomena and the teacher groups. © 2004 Wiley Periodicals, Inc. J Res Sci Teach 41: 432–448, 2004